(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Field experiments were conducted to evaluate the effects of different rates of organo-mineral fertilizers on the growth and yield of selected rice cultivars at two locations: the Teaching and Research Farm of Taraba State University, Jalingo, and Karim Lamido area of Taraba State, North-East Nigeria, during the 2024 cropping season. The experiment used a factorial (2×4×4) arrangement in a Randomised Complete Block Design (RCBD) with three replications. Treatments comprised four upland rice varieties (Faro 44, Faro 58, Faro 59, and local CP) and four fertilizer regimes: 20 t/ha cow dung (organic, OF), 300 kg/ha N.P.K 20:10:10 (inorganic, IF), a 50% cow dung + 50% N.P.K mixture (MX), and an unfertilized control (CT), resulting in 16 treatment combinations. Each plot measured 3 m × 1.5 m with 20 stands, and seedlings were transplanted at 30 cm × 30 cm spacing. Data were collected on tiller number, leaf area, 1000-seed weight, and grain yield. Results showed location significantly (P<0.05) influenced tiller number and yield: Karim Lamido recorded higher tiller numbers (2.7–10.7) and 26.9% greater 1000-seed weight than Jalingo. The highest grain yield (14.19 t/ha) was obtained with 20 t/ha cow dung at Karim Lamido, followed by the 50% mixture (12.26 t/ha), both significantly outperforming the control (8.11 t/ha). Similar yield trends were observed in Jalingo. Overall, the 20 t/ha organic fertilizer and 50% mixture produced comparable yields at both sites. Therefore, applying a 50% organic and 50% inorganic fertilizer blend is recommended to enhance rice yield in the study areas.